Provision of pharmaceutical care by community pharmacists across Europe: is it developing and spreading? - Costa, Filipa A.; Scullin, Claire; Al-Taani, Ghaith; Hawwa, Ahmed F.; Anderson, Claire; Bezverhni, Zinaida; Binakaj, Zahida; Cordina, Maria; Foulon, Veerle; Bikuna, Borja Garcia de; de Gier, Han; Granås, Anne Gerd; et al. (Wiley, 2017)
Rationale, Aims & Objectives: Pharmaceutical care involves patient-centred pharmacist activity to improve medicines management by patients. The implementation of this service in a comprehensive manner, however, requires considerable organisation and effort and indeed it is often not fully implemented in care settings. The main objective was to assess how pharmaceutical care provision within community pharmacy has evolved over time in Europe. Method: A cross-sectional questionnaire-based survey of community pharmacies, using a modified version of the Behavioural Pharmaceutical Care Scale (BPCS) was conducted in late 2012/early 2013 within 16 European countries and compared with an earlier assessment conducted in 2006. Results: The provision of comprehensive pharmaceutical care has slightly improved in all European countries that participated in both editions of this survey (n=8) with progress being made particularly in Denmark and Switzerland. Moreover, there was a wider country uptake, indicating spread of the concept. However, due to a number of limitations, the results should be interpreted with caution. Using combined data from participating countries, the provision of pharmaceutical care was positively correlated with the participation of the community pharmacists in patient-centred activities, routine use of pharmacy software with access to clinical data, participation in multi-disciplinary team meetings and having specialised education. Conclusion: The present study demonstrated a slight evolution in self-reported provision of pharmaceutical care by community pharmacists across Europe, as measured by the BPCS. The slow progress suggests a range of barriers which are preventing pharmacists moving beyond traditional roles. Support from professional bodies and more patient centred community pharmacy contracts, including remuneration for pharmaceutical care services, are likely to be required if quicker progress is to be made in the future.